Predictors of mortality and loss to follow up among children with malignancies in a resource constraint community in Nigeria - Jiya, Fatima B.; Jiya, Nma M.; Jangebe, Mika’ilu A.; Ibitoye, Paul K.; Muhammed, Umar; Yusuf, Tahir; Baba, Jibrin; Adamu, Asma’u; Isezuo, Khadijat O. (International Journal of Contemporary Pediatrics, 2021)
Background: Childhood malignancies are on the increase globally and are of public health concern with associated poor outcome in resource constraint settings. The objective of the study was to determine the factors associated with in-hospital mortality in children with malignant tumours, the predictors of mortality and those of loss to follow up. Methods: A 2 year prospective survey of children aged 1 month-14 years admitted into the paediatric ward of Usmanu Danfodiyo University Teaching Hospital (UDUTH) Sokoto with histologic diagnosis of malignant tumour. Results: There were 26 (74.3%) males and 9 (25.7%) females diagnosed of malignant tumours with male:female=3:1 and mean age at presentation of 6.8±4.0 years. Majority 25 (71.4%) were from low social class. Twenty-four (68.6%) of the subjects had metastasis at presentation. Tumours diagnosed were mainly nephroblastoma 12 (34.3%), rhabdomyosarcoma 09 (25.7%), retinoblastoma 4 (11.4%), and leukaemias 4 (11.4%). Eighteen (51.4%) subjects were discharged after initial course of treatment 15 (42.9%) died and 02 (5.7%) left against medical advice. Of the 18 subjects that were discharged, 16 (88.9%) were lost to follow up. Shock (p=0.01), multiple organ failure (p=0.02), hyperleucocytosis (p=0.04), acute kidney injury (p=0.04) and metastatic disease (p=0.04) were associated with in-hospital mortality. On logistic regression analysis, shock (p<0.001), multiple organ failure (p=0.04) and hyperleucocytosis (p=0.04) were independent predictors of mortality. Residence outside the study location was associated (p=0.04) with loss to follow up. Conclusions: The high in-hospital mortality and loss to follow-up in this study can be reduced by prompt identification and management of oncologic emergencies, and the provision of support services to the children and their caregivers.